Dietary supplementation of betaine for finishing pigs: Review - Valente Júnior, Dante (Pubvet, 2019)
Increasing fat deposition and feed conversion over the days in the finishing phase are factors that directly implicate in pork quality and productive profitability. Nonetheless, heavier pigs result in benefits for the slaughterhouse due lower labor and equipment costs and economic benefits resulting from the dilution of production and processing costs, as well as economic benefits for the pig producer resulting from the dilution of production costs. Therefore, dietary supplementation of betaine for finishing pigs of high lean-genotypes is a strategy to increase lean tissue deposition and minimize fat deposition. Thereby, the aim of this study was to present and discuss the action mechanisms, role and recent results of dietary supplementation of this carcass modifier on performance and carcass traits in finishing pigs. Betaine acts mainly as a methyl groups donor, which increases the methionine availability for protein accretion. On osmoprotective effects, betaine accumulates in cellular organelles, protecting them against osmotic and ionic stresses, which reduce spending energy to keep the cellular homeostasis, becoming an important during the hot periods of the year.